Faktor-Faktor Yang Mempengaruhi Keputusan Anggota Koperasi Dalam Memanfaatkan Jasa Simpan Pinjam Pada KSP Manunggal Tama di Desa Adat Banyualit - Sumiantari, Luh Putu; Suwendra , I Wayan (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This research intends to analyze (1) the factors that influence the decisions of cooperative members in utilizing savings and loan services at KSP Manunggal Tama and (2) the dominant factors influencing the decisions of cooperative members in utilizing savings and loan services at KSP Manunggal Tama. This research uses a type of quantitative research. The data collection technique used was a questionnaire, and the data analysis technique used was factor analysis. The sample in this research is members of the KSP Manunggal Tama cooperative with technical means of purposive sampling. The number of samples in the study was 155. The results of this research indicated that (1) the factors that influence the decisions of cooperative members in utilizing savings and loan services are management trust factors and ease of administration, and (2) the dominant factors implicate the decisions of cooperative members in utilizing savings and loans at KSP Manunggal Tama as a factor of management's trust in value Varimax Rotation 51.099%.